Pemanfaatan Sistem Informasi Geografik untuk Penentuan Bank Tempat Pembayaran Pajak Bumi dan Bangunan Pelaksana Payment Online System - S Sardana; Rochmad Muryamto (Faculty of Engineering, Universitas Gadjah Mada, 2003)
The research aims to do the spatial analysis in selecting banks for paying land and building tax (Tp banps) which will be nominated as POS banlrs (Payment Online System) banks in Bandung city by applying GIS (Geographic Information Systems) technology.GIS spafial analysis was conducted using three coverages; administrative boundaries of Bandung city, land use, and distibution of TP banlcs, including their corresponding attribute data. verything technique and overlay operations using Arc/Info GIS software were conducted to select the priority of TP banks based on some determined criteria.Nineteen Tp banks were nominated as POS, eight of them were considered as the major priority where their locations are equally distributed in Bandung city.Keywords: tax, geographic information systems, spatial analysis